New Contrast Metric for Realistic Display Performance Measure - Hwang, Alex D. (Dig Tech Pap, 2016)
The contrast ratio (CR) has been used to describe display’s performance. However, CR is unbound, ignores the impact of ambient illumination, or viewer’s contrast perception. We propose new metric for display’s contrast performance based on a modified Weber contrast definition that considers human contrast adaptation and applies for both opaque and see-through displays.